REVIEW BUKU - - Faturochman (Faculty of Psychology Universitas Gadjah Mada, 1998)
Judul Buku: The Roots of Modern Social PsychologyPengarang: Robert M. FarrPenerbit: Blackwell Publisher, OxfordTahun Terbit: 1996